(untitled) (Journal of Training and Development, 2025)
This study was carried out to scrutinize the prospects and challenges of instigating the work-based learning (WBL) approach in TVET in Nepal. A qualitative methodology was adopted for the study. Face-to-face and virtual in-depth interviews were conducted with purposively identified TVET experts, teachers and employers from Nepal. Altogether, there were 15 participants. Primarily, the study addressed two research questions: (i) What are the prospects and challenges for instigating a work-based learning approach in TVET in Nepal, and (ii) How the challenges are tackled? The findings revealed that stakeholders’ readiness and the industry’s volume to meet learners’ needs are key challenges in instigating work-based learning approaches in Nepal. The findings also revealed that the prevailing legal frameworks and practices do not have significant provisions. This urges for a conducive legal framework that makes employers mandatory for providing work-based learning opportunities to TVET students in their industries. The industry volume needs to be increased and strengthened by creating a conducive environment for private sector and foreign investment. Additionally, awareness needs to be made among the stakeholders, especially the guardians and the students, so that the guardians understand the importance of WBL and encourage their children to join and the students to be ready for learning in work-based settings.